Effectiveness of Productive Waqf Management in Improving the Welfare of the Poor: A Bibliometric Review - Judijanto, Loso; Ladjin, Nurjanna; Novitasari, Salwa Aulia (Westscience Press, 2024)
This bibliometric study examines the evolution and thematic concentration within the field of productive waqf management from 2000 to 2024, employing a comprehensive analysis of academic publications to understand the dynamic interplay between Islamic philanthropy and socio-economic development. Through the utilization of citation metrics and VOSviewer tools, the study reveals significant growth in research focusing on the integration of traditional Islamic charitable mechanisms with modern financial tools, notably micro waqf banks and zakat, aimed at enhancing community welfare and poverty alleviation. Collaborative networks among scholars indicate robust intellectual communities with concentrated expertise in specific thematic areas. The findings emphasize the potential of productive waqf in supporting broader economic and social objectives, including alignment with the sustainable development goals (SDGs), and highlight the emerging trend of leveraging technology to increase the transparency and efficiency of waqf management. Challenges in governance and professional management are identified as critical areas needing attention to maximize the impact of waqf. The study proposes future research directions focused on empirical evaluations and the potential impacts of technological innovations in waqf management.